The Application of Signal Detection Theory to Acceptability Judgments - Huang, Yujing; Ferreira, Fernanda (Frontiers in Psychology, 2020)
Acceptability judgments have been an important tool in language research. By asking a native speaker whether a linguistic token is acceptable, linguists and psycholinguists can collect negative evidence and directly test predictions by linguistic and psycholinguistic theories, which provides important insight into the human language capacity. In this paper, we first give a brief overview of this method including: (1) the linking hypothesis for this method, (2) the controversy about the test, and (3) limitations of the current analysis of the results. Then, we propose a new way of analyzing the data: Signal Detection Theory. Signal Detection Theory has been used in many other psychological research areas such as recognition memory and clinical assessments. In this paper, using two examples, we show how Signal Detection Theory can be applied to judgment data. The benefits of this approach are that it can: (1) show how well participants can differentiate the acceptable sentences from unacceptable ones, and (2) describe the participant’s bias in the judgment. We conclude with a discussion of remaining questions and future directions.